Association between physical activity and quality of life in adults - Pucci, Gabrielle Cristine Moura Fernandes; Rech, Cassiano Ricardo; Fermino, Rogério César; Reis, Rodrigo Siqueira (Revista de Saúde Pública, 2012)
OBJECTIVE: To summarize and analyze evidences of the association between physical activity and quality of life. METHODS: Systematic literature review in three electronic databases -PubMed, Lilacs and SciELO- using the following descriptors: "physical activity," "motor activity," "exercise," "walking," "running," "physical fitness," "sport," "life style," "quality of life," "WHOQOL" and "SF." There were selected 38 studies published between 1980 and 2010 that used any instrument to measure physical activity and any version of the Medical Outcomes Study 36-Item Short-Form Health Survey or the World Health Organization Quality of Life to assess quality of life. RESULTS: Most studies reviewed were cross-sectional (68%), 18% experimental, 8% prospective follow-up cohort and 5% mixed-design (cross-sectional and longitudinal). The most widely used questionnaire to assess quality of life was SF-36 (71%), and physical activity was self-reported in 82% of the studies reviewed. Higher level of physical activity was associated with better perception of quality of life in the elderly, apparently healthy adults and individuals with different clinical conditions. CONCLUSIONS: There is a positive association between physical activity and quality of life that varies according to the domain analyzed.